Cerebral blood flow and ventilatory sensitivity to CO2 measured with the modified rebreathing method. - Pandit, J; Mohan, R; Paterson, N; Poulin, M (2008)
The ventilatory response to carbon dioxide (CO2) measured by modified rebreathing (SrVE) is closer to that measured by the steady-state method (SsVE) than is the response measured by Read's rebreathing method. Furthermore, the value estimated by the steady-state method depends upon the number of data points used to measure it. We planned to assess if these observations were also true for cerebral blood flow (CBF), as measured by steady-state (SsCBF) and modified rebreathing (SrCBF) tests. Six subjects undertook two protocols, one in the steady-state and one with modified rebreathing. SsVE depended upon the number of data points used to calculate it, and SsVE and SrVE were similar. However, this was not the case with SsCBF, and SsCBF was much higher than SrCBF. These findings are consistent with the notions that the specific CO2 stimulus differs for CBF control as compared with ventilation (VE) control, and that prior hypocapnia has an effect on CBF and VE for longer than the duration of the hypocapnia.